VD_FINDINFO Décision / 2012 / 80 vom 27. Januar 2012 - VD Tribunal cantonal (2012)
ORDONNANCE DE CONDAMNATION, OPPOSITIONPROCÉDURE, RESTITUTION DU DÉLAI | 354 CPP (CH), 85 al. 1 CPP (CH), 85 al. 4 CPP (CH), 87 al. 3 CPP (CH)